Using synthetic fibres in concrete to control drying shrinkage cracking in concrete slabs-on-grade - Van der Westhuizen, Daniel Erasmus (Stellenbosch : Stellenbosch University, 2013)
Thesis (MScEng)-- Stellenbosch University, 2013.